2015
DOI: 10.1016/j.seizure.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of costs of epilepsy using an electronic practice management software in Germany

Abstract: We were able to demonstrate that electronic practice management software can easily be used to perform long-term health economic evaluations with a bottom-up approach. The combination of both physician- and patient-based electronic databases will facilitate performing less expensive studies, but at the same time simplify large, prospective and multicentre clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 45 publications
4
5
1
Order By: Relevance
“…We could also demonstrate a decrease in carbamazepine prescriptions as the mainly used strong enzyme-inducing AEDs. This is consistent with other European and German studies [33,[37][38][39][40] on prescription patterns in epilepsy that show a strong trend in favor of non-enzyme-inducing drugs.…”
Section: Discussionsupporting
confidence: 92%
“…We could also demonstrate a decrease in carbamazepine prescriptions as the mainly used strong enzyme-inducing AEDs. This is consistent with other European and German studies [33,[37][38][39][40] on prescription patterns in epilepsy that show a strong trend in favor of non-enzyme-inducing drugs.…”
Section: Discussionsupporting
confidence: 92%
“…Our cost calculations were consistent with previous COI studies, which estimated that over 1 year (prevalence based), the direct medical costs related to epilepsy mainly involved the costs of return visits and long-term therapy [17]. A total annual cost of €1698 ($1919) per patient with active epilepsy treated in private neurological offices was reported in Germany [17], whereas the highest annual cost for this patient group was found in the US, at up to $13,787 [8]. Because we are not dealing with chronic epilepsy, the costs of the first seizure work-up are lower.…”
Section: Discussionsupporting
confidence: 88%
“…Both systematic reviews and cost-of-illness (COI) studies have reported a consistent pattern of markedly higher costs associated with those with uncontrolled or refractory epilepsy [1]. Our cost calculations were consistent with previous COI studies, which estimated that over 1 year (prevalence based), the direct medical costs related to epilepsy mainly involved the costs of return visits and long-term therapy [17]. A total annual cost of €1698 ($1919) per patient with active epilepsy treated in private neurological offices was reported in Germany [17], whereas the highest annual cost for this patient group was found in the US, at up to $13,787 [8].…”
Section: Discussionsupporting
confidence: 87%
“…The study has also confirmed findings from other studies on prescription patterns in drug-refractory patients who used a top-down approach ( 38 40 ). Comparison of these prescription patterns with previous German studies carried out in 2003 ( 15 ), 2008 ( 18 ), 2009 ( 38 ), 2011 ( 8 , 41 ), and 2012 ( 9 ) show a significant increase in the use of “newer” AEDs and a marked reduction in enzyme-inducing anticonvulsant prescriptions. Since 2008, German guidelines recommend that the first choice for monotherapy in focal epilepsy should be lamotrigine or levetiracetam and that anticonvulsants with drug–drug interactions should not be used.…”
Section: Discussionmentioning
confidence: 50%